2020
DOI: 10.1002/adfm.202007856
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Multi‐Scale Homogeneous Mixing with Uniform Residence Time Distribution for Rapid Production of Various Metal Core–Shell Nanoparticles

Abstract: Seed‐mediated growth of core–shell nanoparticles, which is conventionally performed in a batch reactor, is successfully reproduced in a microfluidic reactor for a facile production of uniform metal core–shell nanoparticles. The proposed microfluidic design is based on the microstructure inversion for achieving multi‐scale homogeneous mixing with uniform nanoparticle residence time. Simulations demonstrate that among the staggered herringbone microstructures investigated in this study, the upper herringbone (UH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The bimetallic particles often form alloys or core-shell structures and usually exhibit an excellent catalytic performance because of the synergistic effect of metal atoms [104]. For example, Au@Ag core-shell nanoparticles were synthesized (using HAuCl 4 and sodium citrate for the synthesis of Au core, and AgNO 3 and ascorbic acid for the preparation of Ag shell) in a single-phase microreactor (Figure 5a) and a conventional batch reactor, respectively [105]. Compared with the batch results, the spherical Au@Ag core-shell nanoparticles synthesized in the microreactor exhibited a more uniform shell size (Figure 5b,c) due to the faster mixing of reagents and better control over the reaction time.…”
Section: Bimetallic Catalystmentioning
confidence: 99%
“…The bimetallic particles often form alloys or core-shell structures and usually exhibit an excellent catalytic performance because of the synergistic effect of metal atoms [104]. For example, Au@Ag core-shell nanoparticles were synthesized (using HAuCl 4 and sodium citrate for the synthesis of Au core, and AgNO 3 and ascorbic acid for the preparation of Ag shell) in a single-phase microreactor (Figure 5a) and a conventional batch reactor, respectively [105]. Compared with the batch results, the spherical Au@Ag core-shell nanoparticles synthesized in the microreactor exhibited a more uniform shell size (Figure 5b,c) due to the faster mixing of reagents and better control over the reaction time.…”
Section: Bimetallic Catalystmentioning
confidence: 99%
“…Current studies have shown that adding microstructures into microchannels to regulate the local flow field 29,30 can effectively provide a new technical solution for improving the passive mixing efficiency [31][32][33] at the microscale. This approach has been applied to the functional units of microfluidic systems as micromixers 34,35 and microreactors 36,37 . For example, a passive T-shape micromixer with rectangular winglets was developed against the flow direction.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the RIAC is less suitable than other reported techniques for studying nanoparticle formation mechanisms or observing the transport of fluids and chemical species within microchannels. 47–51…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the RIAC is less suitable than other reported techniques for studying nanoparticle formation mechanisms or observing the transport of uids and chemical species within microchannels. [47][48][49][50][51] Building upon our previous study, in the present work we aimed to determine whether the RIAC can be employed as a tool for rapid, reliable and facile production of API nanocrystals. In particular, we report on the design and manufacturing of two different RIAC prototypes, the development of a method for API nanoparticle production using these devices, and a comparison of nanoparticles obtained through this method with those reported in the literature.…”
Section: Introductionmentioning
confidence: 99%